Sarcopenia in the elderly: The importance of resistance training in treatment and prevention (Research, Society and Development, 2023)
The objective of this study was to analyze the effects of resistance exercise programs in the treatment and prevention of sarcopenia in the elderly. An integrative literature review was carried out, with a qualitative approach. Articles published between 2016 and 2023 were selected. The survey was carried out on the platforms: Scientific Electronic Library Online (Scielo), National Library of Medicine (PubMed) Medical Literature Analysis and Retrieval System Online (MEDLINE) and Google Scholar. 9 articles were selected to compose the analysis. The findings showed that resistance exercises proved to be essential for the quality of life of elderly people by delaying sarcopenia. In studies that included resistance exercises alone or combined with aerobic exercises, improvements in muscle mass, muscle strength and performance in functional tests were observed. Resistance exercises are an important intervention to promote the health and quality of life of the elderly. They are effective in preventing and treating sarcopenia, a syndrome that can lead to a range of health problems.